Poly-phenylene jacketed tailor-made dendritic phenylazomethine ligand for nanoparticle synthesis. Issue 20 (18th March 2022) - Albrecht, Ken; Taguchi, Maki; Tsukamoto, Takamasa; Moriai, Tatsuya; Yoshida, Nozomi; Yamamoto, Kimihisa
Abstract : A new design concept of a dendritic ligand with regulated number coordination sites is proposed, and capability as a template for nanoparticle synthesis is demonstrated. Abstract : Synthesizing metal clusters with a specific number of atoms on a preparative scale for studying advanced properties is still a challenge. The dendrimer templated method is powerful for synthesizing size or atomicity controlled nanoparticles. However, not all atomicity is accessible with conventional dendrimers. A new tailor-made phenylazomethine dendrimer (DPA) with a limited number of coordination sites ( n = 16) and a non-coordinating large poly-phenylene shell was designed to tackle this problem. The asymmetric dendron and adamantane core four substituted dendrimer (PPDPA16) were successfully synthesized. The coordination behavior confirmed the accumulation of 16 metal Lewis acids (RhCl3, RuCl3, and SnBr2 ) to PPDPA16. After the reduction of the complex, low valent metal nanoparticles with controlled size were obtained. The tailor-made dendrimer is a promising approach to synthesize a variety of metal clusters with desired atomicity.